SYSTEM LOCK AND CONTROLLING CLASS ROOM DENGAN INTERFACE ANDROID BERBASIS ARDUINO UNO - Endang Sunandar; Khanna Tiara; Mohamad Daud (Universitas Raharja, 2016)
In day-to-day environment, buildings that have a lot of room doors sometimes appears constraints when should lock and unlock all the room one by one, because the security guards had to lock and unlock the doors on each floor of the building space manually. There are several systems that can be tailored to these problems, one of which is a lock and controlling system with Bluetooth facility. In this system using the Bluetooth facility to give commands to the microcontroller used, the namely ATmega328-based ArduinoUno. Users simply open the Bluetooth Controller application and connect to the bluetooth Android smartphone which is mounted on the door, then enter the password